Maternal and fetal outcomes in diabetes mellitus in hospitalized women at a tertiary care institute in South India - Dasari, Papa; Ravichandran, Nithya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Objectives of current study were to find out the proportion of types of diabetes and to know the factors for adverse maternal and fetal outcome in pre-gestational diabetes and gestational diabetes at a tertiary care Institute and to compare the outcomes between pre-gestational diabetes and GDM. Methods: Prospective descriptive study conducted in the department of obstetrics and gynaecology, at a tertiary care center over a period of 1 year. The inclusion criteria were: pre-gestational diabetes (pregnant women with type 1 & type 2 diabetes mellitus) and gestational diabetes mellitus. Exclusion criteria were steroid induced diabetes, tuberculosis, heart disease, autoimmune disorder, chronic renal failure. Statistical analysis: Maternal & fetal outcomes, presence of complications were expressed as proportions and comparison between the 2 groups is done using Chi-square test. Results: Majority of the women (81.5%) were GDM and 18.5% were pre-gestational diabetics (type I DM-5% and Type II-13.5% of total). Past history of GDM was present in 29% of GDM and 31% of type II DM. Sixty percent of GDM and 40% of PGDM were primigravidae. Significantly a greater number of women were obese in PGDM than GDM. Blood sugars were uncontrolled in 20% more so in women with PGDM. Pregnancy loss was more in PGDM when compared to GDM (17.5% vs. 9.1%). Statistically significantly more number with PGDM suffered from hypertension and preterm labour. Conclusions: Obesity, uncontrolled blood sugars, development of hypertension and pre-term labour are the significant factors resulting in adverse maternal and fetal outcomes and these are more common in women with PGDM.